How Does Pubertal Development Impact Caregiver-Adolescent Communication About Sex in Rural, African American Families? An Examination of Mediation Effects. (October 2019) - Ritchwood, Tiarney D.; Metzger, Isha W.; Powell, Terrinieka W.; Corbie-Smith, Giselle; Wynn, Mysha; Lin, Feng-Chang; Akers, Aletha Y.
This study examined the relationship between pubertal development and type of caregiver-adolescent communication about sex (CACS) among 441 African American caregivers participating in an intervention trial in rural North Carolina. We assessed CACS about general sexual health topics and positive aspects of sexuality . Caregivers' attitudes and self-efficacy for CACS, and open communication style were examined as potential mediators. Caregivers engaged in low levels of communication about sex regardless of type. Among caregivers of males, pubertal development was associated with greater communication about general sexual health, which was mediated by self-efficacy for CACS. Among caregivers of females, pubertal development was associated with less communication about general and positive sexual health topics; however, there were no mediating factors. These findings highlight the predictors of CACS among young men and women after pubertal onset. Age appropriate, practical guidance for initiating CACS may be critical for ensuring caregiver talk about sex.